Mapping of Active Frazil for Antarctic Coastal Polynyas, With an Estimation of Sea‐Ice Production - K. Nakata; K. I. Ohshima; S. Nihashi (Geophysical Research Letters)
Abstract The importance of the area of active frazil and associated high sea‐ice production in Antarctic coastal polynyas has been increasingly recognized in recent in situ and high‐resolution satellite observations. However, the occurrence and spatial distribution of active‐frazil area are not well understood. We present the first mapping of active‐frazil area for Antarctic coastal polynyas, based on the thin ice algorithm of AMSR‐E that discriminates active‐frazil area. Mapping of sea‐ice production is presented by taking account of active‐frazil area. Active‐frazil area is predominant along East Antarctica, particularly very close to the coast, locally leading to very high ice‐production rates exceeding 20 m/yr. For frazil‐dominant polynyas, estimated ice production is ∼20%–50% higher compared with previous studies. Analyses of all the major polynyas suggest that active‐frazil extent depends on offshore wind and air temperature, while ice production is determined by offshore wind only.